2016
DOI: 10.1590/s1679-45082016ao3455
|View full text |Cite
|
Sign up to set email alerts
|

Content validity of the Geriatric Health Assessment Instrument

Abstract: Objective Assess the content validity of the Elderly Health Assessment Tool with low education.Methods The data collection instrument/questionnaire was prepared and submitted to an expert panel comprising four healthcare professionals experienced in research on epidemiology of aging. The experts were allowed to suggest item inclusion/exclusion and were asked to rate the ability of individual items in questionnaire blocks to encompass target dimensions as “not valid”, “somewhat valid” or “valid”, using an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…In addition, it reduces the influence of the researcher's opinion on the participant and the cost of the research. 7 Similar to Pedreira, et al 23 we could verify that the panel of evaluators was an essential step to improve the quality of the questionnaire, since it increased the clarity of the questions, contributing to the instrument to be able to evaluate, in fact, what is intended. The concern about the proper training of the pharmacist for the use of information technology and devices has been discussed in different countries 1,5,9,10,14 and has gained relevance in the face of the increasing number of people who own and use electronic devices that produce health information and the growing institutional databases on health.…”
Section: Receptivity Testmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, it reduces the influence of the researcher's opinion on the participant and the cost of the research. 7 Similar to Pedreira, et al 23 we could verify that the panel of evaluators was an essential step to improve the quality of the questionnaire, since it increased the clarity of the questions, contributing to the instrument to be able to evaluate, in fact, what is intended. The concern about the proper training of the pharmacist for the use of information technology and devices has been discussed in different countries 1,5,9,10,14 and has gained relevance in the face of the increasing number of people who own and use electronic devices that produce health information and the growing institutional databases on health.…”
Section: Receptivity Testmentioning
confidence: 66%
“…18 The degree of agreement between the evaluators about relevance and clarity was superior to 80% in both evaluation cycle indicating that the questionnaire was sufficiently clear and relevant to be used to a survey. 23 The suggestions received were essential for the improvement of the questionnaire and contributed to the results of the acceptance test and answers obtained in the final collected data. Similarly, we believe that the electronic format facilitated the process of capturing the answers, because it is possible for the participant to choose the best time to respond.…”
Section: Receptivity Testmentioning
confidence: 99%
“…It shows that the component has a strong connection to the mobility problems that occur in the elderly with the ICC value of 0.922. Studies conducted by Pedreira, Rocha, Santos, Vasconcelos, and Reis, (2016), showed that the average value of the validity of the instrument used to assess the health status of the elderly is 0.934. It shows that the elderly health status assessment instrument can be used and developed in order to identify the various problems faced by the elderly and assist in determining a strategy associated with the health of the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…For data analysis and validation of the online forum, the Content Validity Index (CVI) was used. 9 In addition to the statistical analysis from the CVI, an evaluation of each observation, suggestion or critique made by the experts was performed.…”
Section: /15mentioning
confidence: 99%